2007
DOI: 10.1016/s0030-6657(07)70561-9
|View full text |Cite
|
Sign up to set email alerts
|

Ocena odsetka limfocytów CD19+CD5+ w przerosłych migdałkach gardłowych u dzieci chorych na wysiękowe zapalenie ucha środkowego

Abstract: The significant higher percentage of B lymphocytes with expressions of CD5+ receptor in hypertrophied adenoid tissue at children with otitis media with effusion are important to develop of early immunological response to inflammatory state in middle ear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…It has been shown that the accelerated apoptosis of PBMCs adversely affects the immune system, causing depressed human immunity [41], which may finally lead to autoimmune diseases, such as type 1 diabetes, allergy, or asthma, as well as cancer development [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the accelerated apoptosis of PBMCs adversely affects the immune system, causing depressed human immunity [41], which may finally lead to autoimmune diseases, such as type 1 diabetes, allergy, or asthma, as well as cancer development [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that accelerated apoptosis of PBMCs may be associated with adverse changes in the immune system, such as depleted human immunity [39], which, in consequence, may lead to the development of autoimmune diseases (type 1 diabetes, asthma, allergy) and cancer [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Different degrees of airway obstruction may lead to the development of an abnormal pattern of breathing through the mouth (oral respiratory pattern). Impaired ventilation and exchange of air through the nose can increase the risk of secretory otitis media or chronic rhinitis [2]. A consequence of the latter is the obstruction of posterior nares, and the impaired patency of the Eustachian tube pharyngeal orifice.…”
mentioning
confidence: 99%